2014
DOI: 10.5012/bkcs.2014.35.8.2257
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Thermal Performance of Fullerene-Based Lead Salt

Abstract: C60 is widely investigated because of its unique structure. But its applications in solid propellant seem to be relatively neglected. C60 has more outstanding features than carbon black which is widely used as a catalyst ingredient of solid propellant. To combine the advantages of fullerene and lead salts, another good composite in propellant catalysts, we synthesized a kind of fullerene phenylalanine lead salt (FPL) and explored its thermal performances by differential thermal analysis (DTA) and thermogravime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…114 It was further found that FHN can also accelerate the decomposition of RDX and HMX. The peak temperatures of the exothermal decomposition of these nitramines were reduced 117 and the corresponding E a of RDX was decreased by 17 kJ mol −1 , while that of HMX was reduced by more than 20 kJ mol −1 . In addition to stabilizing common explosives, CNTs also have a significant influence on the stability of energetic binders.…”
Section: Effects Of Cnms On Performances Of Emsmentioning
confidence: 85%
See 3 more Smart Citations
“…114 It was further found that FHN can also accelerate the decomposition of RDX and HMX. The peak temperatures of the exothermal decomposition of these nitramines were reduced 117 and the corresponding E a of RDX was decreased by 17 kJ mol −1 , while that of HMX was reduced by more than 20 kJ mol −1 . In addition to stabilizing common explosives, CNTs also have a significant influence on the stability of energetic binders.…”
Section: Effects Of Cnms On Performances Of Emsmentioning
confidence: 85%
“…34, at least two steps are involved in the decomposition of these fullerene derivatives, which started between 100 and 150°C. In particular, FPL undergoes a fourstep exothermic process starting at 135°C, 117 which can reduce the decomposition T p of RDX by more than 20°C and decrease E a by 30 kJ mol −1 . FHN undergoes at least four decomposition steps, under a N 2 atmosphere, starting at around 150°C, while FEN decomposes in only two steps, as described above.…”
Section: Effects Of Cnms On Performances Of Emsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 It was mentioned that the promotion of the thermal decomposition process by the nanosized CuO and NiO shows a strong effect on decreasing the decomposition temperatures of nitramine or AP as oxidizers. 12 The carbon nanomaterials including carbon nanotubes (SWCNT and MWCNT), 13 graphene sheets (GS, GO, and rGO), 14−18 and fullerenes 19,20 are novel materials that can be used to improve thermal conductivity, heat release, and reactivity of various energetic materials (EMs). They help to achieve the desired performances, but certainly, they are usually not so cost-effective due to complicated technology for production.…”
Section: Introductionmentioning
confidence: 99%